2019
DOI: 10.4236/ojmn.2019.91004
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Retinal Nerve Fiber Layer and Ganglion Cell Complex after Optic Chiasmal Decompression

Abstract: This paper is an attempt to ascertain the role of the optical coherence tomography by measuring the retinal nerve fiber layer thickness and ganglion cell complex area to predict postoperative visual outcome after chiasmal decompression. 16 eyes scheduled for chiasmal decompression surgery were assessed before and 3 months after surgery with standard automated perimetry and OCT (optical coherence tomography). Preoperative RNFL (retinal nerve fibre layer) thickness and GCC (ganglion cell complex) area were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Retinal cells are closely interacting with each other and the death of a single cell releases glutamate which triggers an excitotoxic cascade, resulting in nitric oxide production and other metabolite deregulation affecting the survival of surrounding cells ( Pietrucha-Dutczak et al, 2018 ). In the present study, global GCC thickness decreased over time; such reduction was less significant than RFNL thinning, which is in accordance with Salah’s study ( Salah and Ali, 2018 ). VEP amplitude increasing after decompression due to axonal traffic unblocking was more significant than structural variation, so electrophysiology sensed vision recovery better than OCT.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Retinal cells are closely interacting with each other and the death of a single cell releases glutamate which triggers an excitotoxic cascade, resulting in nitric oxide production and other metabolite deregulation affecting the survival of surrounding cells ( Pietrucha-Dutczak et al, 2018 ). In the present study, global GCC thickness decreased over time; such reduction was less significant than RFNL thinning, which is in accordance with Salah’s study ( Salah and Ali, 2018 ). VEP amplitude increasing after decompression due to axonal traffic unblocking was more significant than structural variation, so electrophysiology sensed vision recovery better than OCT.…”
Section: Discussionsupporting
confidence: 93%
“…Tieger et al described persistent damage in the nasal sector at 1-year follow-up in eight patients that attended surveillance visits ( Tieger et al, 2017 ). Other authors also reported the thinning of RFNL and global GCC ( Moon et al, 2011 ; Salah and Ali, 2018 ; Poczos et al, 2022 ). Our results presented in Table 3 data are consistent with the abovementioned findings, and global RNFL and, in less degree, GCC still decrease after surgery (p < 0.05).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations